Reprogramming mouse fibroblasts into engraftable myeloerythroid and lymphoid progenitors - Hui Cheng; Heather Yin-Kuan Ang; Chadi A. EL Farran; Pin Li; Hai Tong Fang; Tong Ming Liu; Say Li Kong; Michael Lingzi Chin; Wei Yin Ling; Edwin Kok Hao Lim; Hu Li; Tara Huber; et al. (Nature Communications, 2016)
Direct reprogramming of closely-related lineages can generate hematopoietic stem cells. Here, the authors show hematopoietic transcription factors Scl, Lmo2, Runx1 and Bmi1 can reprogram fibroblasts into induced hematopoietic progenitors (iHPs), which are engraftable blood progenitors.